Analysis in the Directly Observed Treatment Short-course (DOTS) Strategy implementation in children with pulmonary tuberculosis in Mataram-Indonesia: A qualitative study - Saimi, Saimi; Ariyanti, Ayu Deny; Karjono, Muhammad; Khalik, Lalu Abdul (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Tuberculosis is a global health problem, especially in children. Handling child TB cases in Mataram City, in 2022 there will be 184 TB cases in children and in 2023 there will be an increase of 310 cases. Reporting records experienced treatment failure of 43.7%, this condition indicates the phenomenon of implementing the DOTS program in the treatment of TB patients in children. Purpose: To analyse the implementation of the Directly Observed Treatment Shortcourse (DOTS) programme in the treatment of children with pulmonary tuberculosis. Method: Qualitative research with an exploratory descriptive design conducted on children with pulmonary tuberculosis in Mataram City. The sources of data and information were 13 informants consisting of: Persons in charge of the TB program at the Health Service, Hospitals, namely pediatricians, Community Health Center TB program holders, Medicine Drinking Supervisors and families of TB sufferers. In-depth interview methods and data analysis through reduction and triangulation, as well as document searches to record and report the implementation of DOTS program activities, including identification and diagnosis, classification and staging of TB, treatment of pediatric TB, treatment, monitoring and evaluation, prevention and education, handling side effects, and drug-resistant TB (TB-RO). Results: The implementation of the DOTS program in handling TB in children is still not in accordance with the SOP. Active screening of new case detection rates is still low, the readiness of professionals in identification and diagnosis, classification and staging of pediatric TB have not run optimally, the implementation process is carried out with a tiered referral system, the logistics of tools and drugs often occur out of stock, TB-RO and drug allergies are found to not be handled properly. Public compliance in treatment is still low and stigmatization is high in society. The government's commitment to handling pulmonary TB patients in children has not been implemented properly. Conclusion: The implementation of the Directly Observed Treatment Short-course (DOTS) program has not been optimal. The government's commitment to handling TB cases in children has many obstacles and challenges, limited professional human resources, running out of medicines, high absenteeism of TB patients, and high stigmatization of TB disease in society.